2016
DOI: 10.1017/fmp.2016.6
|View full text |Cite
|
Sign up to set email alerts
|

The Logarithmically Averaged Chowla and Elliott Conjectures for Two-Point Correlations

Abstract: Let λ denote the Liouville function. The Chowla conjecture, in the two-point correlation case, asserts thatas x → ∞, for any fixed natural numbers a 1 , a 2 and nonnegative integer b 1 , b 2 with a 1 b 2 −a 2 b 1 = 0. In this paper we establish the logarithmically averaged versionof the Chowla conjecture as x → ∞, where 1 ω(x) x is an arbitrary function of x that goes to infinity as x → ∞, thus breaking the 'parity barrier' for this problem. Our main tools are the multiplicativity of the Liouville function at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
209
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(215 citation statements)
references
References 33 publications
5
209
0
1
Order By: Relevance
“…. One can bound this by the probability that γ (k) = γ (k), where γ , γ are selected as in the proof of (15). But if we fix the variables p 1 , .…”
Section: /200mentioning
confidence: 99%
See 2 more Smart Citations
“…. One can bound this by the probability that γ (k) = γ (k), where γ , γ are selected as in the proof of (15). But if we fix the variables p 1 , .…”
Section: /200mentioning
confidence: 99%
“…The further study of this random graph (or similar such graphs) may have some further applications; in particular, one may hope to use expansion properties of this graph to make progress towards the k = 2 case of the Chowla conjecture (Conjecture 1.3). In fact by pursuing this direction further, the third author has recently shown that a logarithmic form of Chowla's conjecture holds, and consequently that the logarithmic density of integers n for which (µ(n), µ(n + 1)) = (ε 1 , ε 2 ) exists (see [15]). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To do this, we use a recent result of the author [21] regarding correlations of multiplicative functions: Theorem 1.10 (Logarithmically averaged nonasymptotic Elliott conjecture). [21, Theorem 1.3] Let a 1 , a 2 be natural numbers, and let b 1 , b 2 be integers such that a 1 b 2 − a 2 b 1 = 0.…”
Section: Example 17 (Numerical Examples)mentioning
confidence: 99%
“…Attention is drawn to application of a (recent) result of Tao [24], that a sufficiency of large sums…”
mentioning
confidence: 99%